Peran Pendidikan Indonesia di Era Society 5.0 - Daffa Faqiha Fawwaz Hanjowo, Mochammad; Athahirah, Nuke; Febrianto Saputra, Ryan; Al-Farisi, Salman; Wijaya Abdul Rozaq, Rama (Jurnal Etnik: Ekonomi-Teknik, 2023)
Society 5.0 is based on the concept of integration between humans and technology, where technology is used as a means to improve human quality of life. This can be achieved through the use of advanced technologies such as AI and IoT, which are capable of effectively and efficiently collecting, analyzing, and optimizing information and resources. In Indonesia, the education sector plays a crucial role in preparing students for the new era called Society 5.0. However, there are still many challenges that Indonesian education will face when encountering the smart Society 5.0 era, such as limited infrastructure and a lack of understanding of the concept of Society 5.0. Therefore, this research was conducted to determine the readiness of Indonesian education in facing the Society 5.0 era. This research used a qualitative approach with data collection through a questionnaire with several participants directly involved in education and information technology learning. The results of the study show that Indonesian education still faces many challenges. Currently, the government is seeking solutions to improve the quality of education in Indonesia in facing the future.